Strategi Pemberdayaan Masyarakat dalam Mitigasi Bencana Melalui Jabar Resilience Culture Province di Jawa Barat Community Empowerment Strategy in Disaster Mitigation Through West Java Resilience Culture Province in West Java - Kusumawati, Riny (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2024)
The West Java Resilience Culture Province (JRCP) program is designed to foster a culture of disaster awareness and resilience among the people of West Java in their response to disasters. JRCP aims to create a prepared society by leveraging technology and infrastructure development as effective mitigation measures. Community empowerment plays a vital role in disaster mitigation, facilitating individuals, families, and communities to take responsibility for disaster risk reduction. This approach also develops their ability to actively participate in disaster risk reduction efforts, fostering a motivation to recognize and address potential disaster threats and risks. The research focuses on two main aspects which are building community awareness in disaster mitigation and enhancing community capacity for disaster response. A qualitative approach using the case study method is employed for this research. Informants were selected through purposive sampling, ensuring they met specific research criteria. Data collection involved interviews, and the analysis was carried out using descriptive analysis techniques. The research findings highlight the various approaches to community empowerment in disaster mitigation. These include building community awareness through targeted socialization activities to impart knowledge about disaster risks and their management. Keywords: Community, disaster awareness, disaster mitigation.